The relation between monetary policy and the stock market in Europe - Helmut Lütkepohl; Aleksei Netšunajev (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
We use a cointegrated structural vector autoregressive model to investigate the relation between euro area monetary policy and the stock market. Since there may be an instantaneous causal relation we consider long-run identifying restrictions for the structural shocks and also use (conditional) heteroskedasticity in the residuals for identification purposes. Heteroskedasticity is modelled by a Markov-switching mechanism. We find a plausible identification scheme for stock market and monetary policy shocks which is consistent with the second order moment structure of the variables. The model indicates that contractionary monetary policy shocks lead to a long-lasting down-turn of real stock prices.
Keywords: C32; 330; cointegrated vector autoregression; heteroskedasticity; Markov-switching model; monetary policy analysis